On Performance of Filter used for Interference Mitigation between LTE and DVB-T Networks in Digital Dividend Spectrum - Tekovic, Alberto; Bonefacic, Davor; Nad, Robert; Pidanič, Jan; Němec, Zdeněk (Croatian Society Electronics in Marine - ELMAR, 2016)
This paper concerns interference mitigation techniques caused by Long Term Evolution (LTE) mobile system operating in Digital Dividend into Digital Video Broadcasting Terrestrial (DVB-T) system. Use of filtering as one of the most effective interference mitigation methods has been investigated. Laboratory measurements have been conducted for several commercially available LTE filters in order to determine their performance while exposed to variable ambient temperature.
Účinnost filtrace pro omezení interferencí mezi LTE a DVB-T v uvolněných frekvenčních pásmech
Keywords: LTE; DVB-T; Digital Dividend; interference mitigation; adjacent channel; cutoff frequency; filtering; LTE; DVB-T; Digitální dividenda; interference; sousední kanály; mezní frekvence; filtrace